Thīralưk nư̄ang nai ngān chāpanakit sop ʻĀčhān Yāčhai Ruttharakān, Wō̜thō̜. Mō̜. (Khēmī). - Yāčhai Ruttharakān, 1918-1982 ([Bangkok] : [Kanlayānī Ruttharakān], 1983)
Cremation volume for Yāčhai Ruttharakān, 1918-1982, Thai woman; includes a biography, condolences and formulas for traditional Thai medicines.
"Tamrā yāklāngbān (mī sapphakhun changat) / dōi Phra Thēpwimonmōlī (Bunmā)": 284 p. (2nd group).
Keywords: Yāčhai Ruttharakān, -- 1918-1982 -- Death and burial; Traditional medicine -- Thailand -- Formulae, receipts, prescriptions; Herbs -- Therapeutic use -- Thailand; College teachers -- Thailand -- Biography